Integrasi TPACK (Technological, Pedagogical, and Content Knowledge) Dalam Pembelajaran Matematika Materi Bentuk Aljabar - Musdalifa Musdalifa; Ariantje Dimpudus (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This literature aims to present the integration of TPACK (Technological, Pedagogical, And Content Knowledge) in mathematics learning and see its role in increasing learning effectiveness. By conducting analysis from various relevant sources of articles, journals and previous research, we can identify the benefits of integrating TPACK in mathematics learning in algebra form material. The results of this literature analysis show that there is a positive impact in increasing the effectiveness and abilities of students. The combination of technology, pedagogy and content knowledge makes mathematics learning able to provide a more interactive learning experience. It is hoped that this article can be a helpful reference for educators and educational researchers who are interested in implementing TPACK in the learning process to increase learning effectiveness.